Impact of Antigen Presentation Mechanisms on Immune Response in Autoimmune Hepatitis - Fasano, Rossella; Malerba, Eleonora; Prete, Marcella; Solimando, Antonio Giovanni; Buonavoglia, Alessio; Silvestris, Nicola; Leone, Patrizia; Racanelli, Vito (Frontiers in Immunology, 2022)
The liver is a very tolerogenic organ. It is continually exposed to a multitude of antigens and is able to promote an effective immune response against pathogens and simultaneously immune tolerance against self-antigens. In spite of strong peripheral and central tolerogenic mechanisms, loss of tolerance can occur in autoimmune liver diseases, such as autoimmune hepatitis (AIH) through a combination of genetic predisposition, environmental factors, and an imbalance in immunological regulatory mechanisms. The liver hosts several types of conventional resident antigen presenting cells (APCs) such as dendritic cells, B cells and macrophages (Kupffer cells), and unconventional APCs including liver sinusoidal endothelial cells, hepatic stellate cells and hepatocytes. By standard (direct presentation and cross-presentation) and alternative mechanisms (cross-dressing and MHC class II-dressing), liver APCs presents self-antigen to naive T cells in the presence of costimulation leading to an altered immune response that results in liver injury and inflammation. Additionally, the transport of antigens and antigen:MHC complexes by trogocytosis and extracellular vesicles between different cells in the liver contributes to enhance antigen presentation and amplify autoimmune response. Here, we focus on the impact of antigen presentation on the immune response in the liver and on the functional role of the immune cells in the induction of liver inflammation. A better understanding of these key pathogenic aspects could facilitate the establishment of novel therapeutic strategies in AIH.